IMPLEMENTATION OF SCHOOL-BASED MANAGEMENT BASED ON SPIRITUAL VALUES AS A STRATEGY TO IMPROVE THE QUALITY OF LEARNING: CASE STUDY AT JUNGKAL ELEMENTARY SCHOOL LAMPIHONG DISTRICT BALANGAN REGENCY SOUTH KALIMANTAN: Implementasi Manajemen Berbasis Sekolah Berlandaskan Nilai-Nilai Spiritual sebagai Strategi untuk Meningkatkan Kualitas Pembelajaran: Studi Kasus di SD Jungkal Kecamatan Lampihong, Kabupaten Balangan, Kalimantan Selatan - Muhammad Ihsan; Muhammad Syukri; Safaruddin Safaruddin; Muhammad Mochtar Mandala Silam; Syahrial Shaddiq (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyze the implementation of school-based management grounded in spiritual values as a strategy to improve learning quality at SDN Jungkal, Lampihong District, Balangan Regency. This research employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation. Data analysis used data reduction, data display, and conclusion drawing techniques. The results showed that the implementation of school-based management grounded in spiritual values was carried out through the integration of religious values in school program planning, learning implementation, and educational evaluation. Spiritual values were applied through religious habituation activities, strengthening student character, and school leadership emphasizing moral role modeling. This implementation had a positive impact on improving learning quality, particularly in character development, increasing learning motivation, and creating a conducive learning environment. Supporting factors included school community commitment and community support, while inhibiting factors included limited supporting facilities and program implementation consistency.